The Sweet Side of Immune Evasion: Role of Glycans in the Mechanisms of Cancer Progression - Nardy, Ana Flávia Fernandes Ribas; Freire-de-Lima, Leonardo; Freire-de-Lima, Célio Geraldo; Morrot, Alexandre (Frontiers in Oncology, 2016)
Glycans are part of the essential components of a cell. These compounds play a fundamental role in several physiopathological processes including cell differentiation, adhesion, motility, signal transduction, host-pathogen interactions, tumor cell invasion and metastasis development. Glycans are also able to exert control over the changes in tumor immunogenecity, interfering with tumor editing events and leading to immune resistant cancer cells. The involvement of glycans in cancer progression are related to glycosylation alterations. Understanding such changes is, therefore, extremely useful to set the stage for their use as biomarkers, improving the diagnostics and therapeutic strategies. Herein, we discuss the basis of how modifications in glycosylation patterns may contribute to cancer genesis and progression as well as their importance in oncology field.